PENGDOKUMENTASIAN SITUS MEGALITIK SEBAGAI WARISAN BUDAYA RAWAN PUNAH DI KABUPATEN NIAS BARAT - SUMATERA UTARA - Ulul Azmi (CARITA: Jurnal Sejarah dan Budaya, 2025)
Megalithic sites are cultural objects left behind by humans in ancient times which are not only in the form of buildings made of large stones but also small stones as long as they are used to worship ancestors or forefathers. The tangible and intangible cultural heritage as well as the megalithic sites in West Nias are one of the cultural heritages prone to extinction that must be maintained and preserved. The focus of this research is material cultural heritage, namely megalithic sites spread across West Nias Regency and intangible cultural heritage. This research uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. Data analysis techniques are carried out using qualitative analysis techniques which include data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, for data validity techniques, researchers use data and method triangulation techniques. The results of this research state that the Megalithic Sites in West Nias are spread across 5 sub-districts and are found in several villages, namely (a) Megalithic Sites in Mandhrehe District: Simaeasi Village Megalithic Site, Tekhembowo Megalithic Site, Hiligoe Megalithic Site, Lologulo Marga Gulo Village Megalithic Site, and Tuhemberua Megalithic Site (b) North Mandrehe District Megalithic Site: Balodano Megalithic Site, Osa Osa Megalithic Site (c) Ulu Moro'o District Megalithic Site: Hili Lawelu Megalithic Stone, Behu Marga Waruwu Megalithic Stone, (d) Lolofitu District Megalithic Site Moi: Wango Village Megalithic Stone and Ara Fundrako Megalithic Site Waruwu Marga (e) Gowawambea Megalithic Site and seven other points.